IQZATH Theory: Reconstructing Islamic Economics toward a Moral-Spiritual and Sustainable Paradigm - Muhammad Fauzinudin Faiz; Wildan Miftahussur (Journal of Islamic Studies and Education, 2026)
The rapid growth of Islamic economics has strengthened Sharia-compliant finance, halal industries, and Islamic social finance. However, its theoretical development remains constrained by the absence of an integrated framework explaining how spiritual consciousness generates ethical governance and sustainable economic outcomes. Existing paradigms largely emphasize legal compliance, institutional governance, and normative objectives while offering limited explanation of the causal mechanisms linking individual moral transformation to organizational governance and long-term sustainability. This study develops IQZATH Theory (Iqtishādiyyah az-Zakiyyah ath-Ṭāhirah) as a novel middle-range theoretical framework for reconstructing Islamic economics from a moral-spiritual perspective. Employing a qualitative conceptual design with a theory-building approach, the study synthesizes interdisciplinary literature on Islamic economics, governance, business ethics, sustainability, and Islamic philosophy through ontological, epistemological, and axiological analyses. The proposed framework identifies tazkiyah (spiritual purification) as the foundational causal mechanism that fosters Nazahah (ethical integrity), Syaffafah (institutional transparency), public trust, and ultimately Istidamah (sustainable governance). Unlike existing approaches that primarily prescribe normative ideals, IQZATH explains how spiritual values are transformed into institutional behavior through an integrated causal process connecting the individual, organizational, and societal levels. The theory contributes to Islamic economic scholarship by repositioning spirituality as an endogenous explanatory construct rather than merely a normative principle, thereby extending international discussions on ethical governance and sustainable development. Future empirical research is encouraged to operationalize and validate the proposed constructs across diverse institutional and cross-cultural settings.